Efektivitas Pembelajaran Probing-Prompting Berbasis Etnomatematika Terhadap Kemampuan Literasi Matematika - Himmatul Ulya; Ratri Rahayu (Universitas Sebelas Maret, 2018)
The mathematics learning applied by teacher have not been able to engage students to apply concepts to solve daily problems. Beside that, students are not used to face a higher order thingking problems. It created a lack of mathematics literacy. This research aims to (1) know to what extent implementatioan etnomathematic-based probing-prompting learning on mathematics literacy, (2) know to wheather students taught by etnomathematic-based probing-prompting learning have higher mathematics literacy than students taught by expository, and (3) know the improvement of students’ mathematics literacy after implementatioan of etnomathematic-based probing-prompting learning. This is an experimental research by using nonequivalent control group design. It was conducted in NU Nawa Kartika Kudus elementary school in even semester of 2016/2017academic year. The collecting data technique used is a test to measure the students’ mathematics literacy. The analysis techniques in this research included student test (t-test), and gain test to measure the improvement of students’ mathematics literacy. The result of this research were (1) students’ mathematics literacy was achived the passing grade after implementatioan of etnomathematic-based probing-prompting,(2 ) the average of students’ mathematics literacy taught by etnomathematic-based probing-prompting learning was higher than students taught by expository, and (3) students’ mathematics improve by 54% after implementatioan of etnomathematic-based probing-prompting learning or categorized as middle level